Strategi Digitalisasi Manajemen Resiliensi dalam Mendukung Hilirisasi Modul Bahasa Arab 5.0 Yang Berkelanjutan: Strategi Digitalisasi Berbasis Ketahanan untuk Penyebaran Modul Bahasa Arab yang Berkelanjutan - Nurul Aini Pakaya; Wahyudin Hasyim; Febrianto Hakeu (Language Development Center, 2026)
Background: Background: The Society 5.0 era requires Islamic educational institutions, including Islamic boarding schools, to undergo digital transformation without compromising their identity and scholarly traditions. In the context of Arabic language learning, a managerial strategy is needed to integrate digitalization, resilience management, and module downstreaming, so that learning innovation does not stop at the prototype stage but continues to develop into adaptive and sustainable practices in the pesantren environment. Purpose: Purpose: This study aims to describe the practices of resilience management at Al-Khairaat Islamic Boarding School in Gorontalo City, analyze the digitalization strategy developed to support the sustainable downstreaming of the Arabic Language 5.0 Module, and explain the factors that support and inhibit the sustainability of module downstreaming. Method: This study employed a descriptive qualitative case-study approach. Data were collected through in-depth interviews, participatory observation, and documentation, involving pesantren leaders, Arabic teachers, information technology managers, and students as key informants. Data were analyzed using Miles and Huberman’s interactive model, consisting of data reduction, data display, and conclusion drawing/verification. Data trustworthiness was maintained through triangulation of sources, methods, and time triangulation, and strengthened by member checking. Results and Discussion: The findings show that pesantren resilience management is rooted in traditional values and combined with a vision of institutional modernization. The digitalization strategy is implemented gradually through the use of communication applications, digital academic records, and the development and use of the Arabic Language 5.0 Module in print and digital formats. The sustainable downstreaming process occurs through content adaptation, digital repackaging, and integration into the formal curriculum, with the central role of pesantren leaders, teachers, and IT managers. However, this process still faces infrastructure limitations and disparities in device access. Conclusions and Implications: Conclusions and Implications: The study concludes that the resilience-based digitalization strategy at Al-Khairaat Islamic Boarding School supports the sustainable downstreaming of the Arabic Language 5.0 Module. The practical implication is that pesantren need to strengthen written policies, develop continuous training programs for teachers, and improve the digital ecosystem.